The Chain Reaction of Atmospheric Nitrogen Oxidation, Initiated by an Electric Discharge in Air - Fedotov, V. G.; Fedotova, EYa (My University, 2015)
The data, concerning to the nitrogen oxidation reaction, initiated by electrical discharge, are reviewed in this article. The reviewed data lead to conclusion that critical concentrations of NO molecules and NO3 radicals can be achieved in course of discharge in air at some special conditions, thereafter avalanche-like rise of reaction velocity is observed. At explosion conditions the oxidation of nitrogen proceeds until full exhaustion of atmospheric oxygen in the reaction zone. Explosion like kinetics of nitrogen oxidation results in high concentration of electronically excited molecules NO(B 2Π), it forms conditions for laser generation in the blue region of the spectrum. The generation of this kind was observed. The proposed mechanism of chain reaction explains all the experimental data.
Keywords: Nitrogen oxidation; NO; NO3 radicals; Chain reaction